Developing and Externally Validating a Simple Index Based on the Nonlinear Relationship of Fecal Calprotectin and Long-Term Outcomes in Ulcerative Colitis - Zheng J; Zheng D; Fan Z; Li L; Chen R; Zhang S (Journal of Inflammation Research)
Jieqi Zheng,1,2,* Danping Zheng,1,* Zinan Fan,2,* Li Li,1 Rirong Chen,1 Shenghong Zhang1,3 1Department of Gastroenterology, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou, People’s Republic of China; 3Guangxi Hospital Division of The First Affiliated Hospital, Sun Yat-Sen University, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shenghong Zhang; Rirong Chen, Department of Gastroenterology, The First Affiliated Hospital, Sun Yat-Sen University, 58 Zhongshan Road 2, Guangzhou, People’s Republic of China, Tel +86-20-87755766, Fax +86-20-87332916, Email shenghongzhang@163.com; zhshh3@mail.sysu.edu.cn; chenrr29@mail.sysu.edu.cnBackground: The possible nonlinear association with therapeutic outcomes in ulcerative colitis may contribute to the inconclusive cutoff values of fecal calprotectin (FC). We aimed to explore the nonlinear association between FC levels and long-term therapeutic outcomes in patients with ulcerative colitis and establish a clinically applicable FC index.Methods: We included patients treated with vedolizumab or adalimumab from the VARSITY (n=661) and GEMINI 1 (n=620) studies as discovery and validation cohorts, respectively. The primary outcome was endoscopic remission at week 52 (Mayo Endoscopic Score 0). Restricted cubic splines were used to model nonlinearity between FC and long-term outcomes. Cutoff values were determined using piecewise regression to establish the FC index. Multivariable logistic regression and receiver operating characteristic curve analyses were performed to assess its predictive value.Results: A nonlinear approximate enantiomorphic “J-shaped” association was observed between post-induction FC levels and long-term outcomes. Cutoff values of 180, 500, and 1300 μg/g were selected to construct the FC index; a higher index was significantly associated with a poorer outcome (P for trend < 0.05). Furthermore, the FC index had an area under the receiver operating characteristic curve of 0.7095 [95% CI: 0.6621– 0.7569], 0.6856 [95% CI: 0.6427– 0.7284], 0.7527 [95% CI: 0.7084– 0,7971], and 0.7630 [95% CI: 0.7110– 0.8150] in predicting long-term endoscopic remission, clinical remission, histological remission, and disease clearance, respectively, approximately comparable to continuous FC, and superior to dichotomous FC.Conclusion: The FC index is a promising indicator of therapeutic outcomes and may guide clinicians’ therapeutic decisions.Keywords: fecal calprotectin, ulcerative colitis, nonlinearity, long-term outcome